Blocking KCa3.1 channels increases tumor cell killing by a subpopulation of human natural killer lymphocytes. - Shyny Koshy; Danli Wu; Xueyou Hu; Rajeev B Tajhya; Redwan Huq; Fatima S Khan; Michael W Pennington; Heike Wulff; Patricia Yotnda; Christine Beeton (PLoS ONE, 2013)
Natural killer (NK) cells are large granular lymphocytes that participate in both innate and adaptive immune responses against tumors and pathogens. They are also involved in other conditions, including organ rejection, graft-versus-host disease, recurrent spontaneous abortions, and autoimmune diseases such as multiple sclerosis. We demonstrate that human NK cells express the potassium channels Kv1.3 and KCa3.1. Expression of these channels does not vary with expression levels of maturation markers but varies between adherent and non-adherent NK cell subpopulations. Upon activation by mitogens or tumor cells, adherent NK (A-NK) cells preferentially up-regulate KCa3.1 and non-adherent (NA-NK) cells preferentially up-regulate Kv1.3. Consistent with this different phenotype, A-NK and NA-NK do not display the same sensitivity to the selective KCa3.1 blockers TRAM-34 and NS6180 and to the selective Kv1.3 blockers ShK-186 and PAP-1 in functional assays. Kv1.3 block inhibits the proliferation and degranulation of NA-NK cells with minimal effects on A-NK cells. In contrast, blocking KCa3.1 increases the degranulation and cytotoxicity of A-NK cells, but not of NA-NK cells. TRAM-34, however, does not affect their ability to form conjugates with target tumor cells, to migrate, or to express chemokine receptors. TRAM-34 and NS6180 also increase the proliferation of both A-NK and NA-NK cells. This results in a TRAM-34-induced increased ability of A-NK cells to reduce in vivo tumor growth. Taken together, our results suggest that targeting KCa3.1 on NK cells with selective blockers may be beneficial in cancer immunotherapy.